2020
DOI: 10.4269/ajtmh.19-0720
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability as an Indicator of Autonomic Nervous System Disturbance in Tetanus

Abstract: Autonomic nervous system dysfunction (ANSD) is a significant cause of mortality in tetanus. Currently, diagnosis relies on nonspecific clinical signs. Heart rate variability (HRV) may indicate underlying autonomic nervous system activity and represents a potentially valuable noninvasive tool for ANSD diagnosis in tetanus. HRV was measured from three 5-minute electrocardiogram recordings during a 24-hour period in a cohort of patients with severe tetanus, all receiving mechanical ventilation. HRV measurements f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Autonomic nervous system dysfunction (ANSD) was defined as at least three of: heart rate >100 beats per minute (bpm), systolic blood pressure >140 mmHg, mean arterial pressure < 60 mmHg, pyrexia > 38°C, and fluctuating blood pressure. All features should be present within one day with no other apparent cause 14 . Sensitivity evaluation of mortality rates within this study was performed by comparing with overall hospital database for outcomes of all patients with tetanus (ICD10 code A35) during the period 2016- 2018.…”
Section: Methodsmentioning
confidence: 99%
“…Autonomic nervous system dysfunction (ANSD) was defined as at least three of: heart rate >100 beats per minute (bpm), systolic blood pressure >140 mmHg, mean arterial pressure < 60 mmHg, pyrexia > 38°C, and fluctuating blood pressure. All features should be present within one day with no other apparent cause 14 . Sensitivity evaluation of mortality rates within this study was performed by comparing with overall hospital database for outcomes of all patients with tetanus (ICD10 code A35) during the period 2016- 2018.…”
Section: Methodsmentioning
confidence: 99%
“…For this study we chose standardised measures of HRV previously found to be of value in patients with tetanus and other cardiovascular syndromes. 16 17 Briefly these are divided into time domain variables (if analysed according to the distribution of RR intervals over time) and frequency domain variables if analysed after Fourier transformation (see figure 1 caption). RR intervals were identified from QRS complexes in ECG recordings using the Pan-Tompkins algorithm 18 implemented in EDFBrowser (https://www.…”
Section: Methodsmentioning
confidence: 99%
“…We specifically selected patients with tetanus as they have significant cardiovascular system disturbance as well as muscle spasms and increased sweating, thus posing a significant challenge for wearable monitors. 16 To evaluate quality of wearablerecorded data, we computed and compared heart rate variability (HRV) data with that from state-of-the-art clinical monitors.…”
Section: Introductionmentioning
confidence: 99%
“…The variation in heart rate is caused by the alternation in sympathetic and parasympathetic control of the heart. Thus, HRV can also be used to demonstrate neural modulation activity on the cardiac system. , For patients at risk for heart disease, HRV serves as a reliable metric for assessing whether the heart is beating properly. For instance, the identification of arrhythmia, myocardial infarction, and other CVDs can be done through ECG signal interpretation and HRV analysis.…”
Section: Cardiac Biomarkers and Sensing Signalsmentioning
confidence: 99%